Pola Sebaran Populasi Azotobacter sp dan Bahan Organik pada Berbagai Kelas Kemiringan Lereng Perkebunan Teh Dataran Tinggi PPTK Gambung (Population Distribution Pattern of Azotobacter sp and Organic Material on Variety Slope Classification of Tea Highland - Eko PRANOTO; Sulistiawati PRATIWI; Hani WACHYUNI; Sastrika ANINDITA (Biospecies, 2015)
The purpose of this experiment was to identified the population distribution of Azotobacter sp and organic matter on variety slope classification at experimental field, PPTK Gambung, West Java. The methode that used was exploration method. PPTK Gambung’s tea plantation has three class of slope, they are slope of <8% (flat-rather slope slighty), 8-15% (slope slighty), and 16-25% (rather steep). Total 14 composite soil sample taken from each of the class to analyze total population of Azotobacter sp, average of organic matter soil content, and water content average. Sample was taken based on sample point in Land Unit Map (SPL). Slopes <8% (flat-rather slope slighty) have total population of Azotobacter sp around 7,14x107 cfu/gram soil, water content 5,97%, and organic matter 10,68%. Slopes 8-15% (slope slighty) have total population of Azotobacter sp around 10,38x107 cfu/gram soil, water content 6,47%, and organic matter 10,91%. And slopes 16-25% (rather steep) have total population of Azotobacter sp around 11,75x107 cfu/gram soil, water content 6,34%, and organic matter 10,65%.